Ebla and beyond ancient Near Eastern studies after fifty years of discoveries at Tell Mardikh : proceedings of the international congress held in Rome, 15th-17th December 2014 - Matthiae, Paolo 1940-; Pinnock, Frances 1950-; D'Andrea, Marta (Wiesbaden Harrassowitz Verlag, 2018)
Cover -- Title Pages -- Imprint -- CONTENTS -- PROGRAM -- Maamoun ABDULKERIM: Greeting Address -- Frances PINNOCK: Opening Speech -- Michel AL-MAQDISSI: Notes d'Archéologie Levantine LII. Remarques introductives sur des Archives de R. du Mesnil du Buisson conservées au DAO du Musée du Louvre -- Agnese VACCA: Centralization Before the Palace. The EB III-IVA1 Sequence on the Acropolis of Tell Mardikh/Ebla -- Corinne CASTEL: Urban Planning and Urbanization in 3rd Millennium BC Syria. Tell Al-Rawda in Context -- Walther SALLABERGER: Kura, Youthful Ruler and Martial City-God of Ebla -- Pascal BUTTERLIN: From Mari to Ebla, Designs of Interculturality? -- Manfred KREBERNIK: Syllables in Eblaite and their representation -- Lisa COOPER: Half-Empty or Half-Full? Past and Present Research on EB IV Caliciform Goblets and their Chronological and Socio-Economic Implications -- Benjamin FOSTER: The Akkadian Adventure in Syria -- Marta D'ANDREA: The Early Bronze IVB Pottery of Ebla: Stratigraphy, Chronology, Typology and Style -- Mohammed ALKHALID: One Hundred Years of Change at Ebla. The Pottery Assemblages between the 3rd and the 2nd Millennium BC -- Ahmed Fatima KZZO: Cappadocian Style Seals at Ebla -- Davide NADALI: Inward/Outward: A Re-Examination of the City-Gates at Ebla -- Andrea POLCARO: Urban Landscape and Funerary Ideology in Old Syrian Ebla -- Jean-Marie DURAND: Les textes d'Ébla "paléobabylonienne -- Grégory CHAMBON: La mesure de longueur "coudée" à Mari Amorrite -- Adelheid OTTO: Basins in the Temples of Ebla, Syria and Upper Mesopotamia: An Essential Cult Requisite? -- Marian FELDMAN: Tracing Northern Networks among the Arts of Syria in the Middle and Late Bronze Ages -- Glenn M. SCHWARTZ: TZhe Value of the Vestigial: From Middle to Late Bronze in Ebla and Western Syria
Sara PIZZIMENTI: Ebla in the Iron Age: New Evidence from the Acropolis. Remarks from a Work in Progress -- Maria Gabriella MICALE: Clay Figurines in the Persian Achaemenid Near East as Seen from Tell Mardikh -- Paolo MATTHIAE: Final Considerations
Includes bibliographical references. Description based on print version record
Keywords: Middle East ; Antiquities; Ebla (Extinct city) ; Antiquities; Electronic books; Konferenzschrift -- 2014 -- Rom